Mortar for pavement slab bottom void grouting repair and preparation method thereof

By optimizing the composition and proportion of the mortar, the early strength, fluidity and anti-permeability properties of the cement mortar are improved, the problems of insufficient fluidity and early strength of the mortar in the existing technology are solved, and an efficient and economical repair effect is achieved.

CN119330673AInactive Publication Date: 2025-01-21SHANTOU UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411885216.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-01-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

When repairing pores under cement mortar, existing cement mortar often has problems such as insufficient fluidity, insufficient grouting performance, insufficient early strength and shrinkage caused by shrinkage, which is difficult to meet the needs of efficient repair.

Method used

A mortar containing gel material, water, redispersible latex powder, polypropylene fiber, water reducing agent, early strength agent and swelling agent is used to improve the early strength and fluidity of the mortar by optimizing the proportion and combination of these ingredients. and impermeability properties.

Benefits of technology

The compressive strength of this mortar can reach 14.88 MPa in 1 day, the compressive strength in 3 days can reach 77.4% of the 28-day strength, and the flexural strength in 3 days can reach 94.0% of the 28-day strength. It also has high fluidity and micro-expansion. performance, ensuring the uniformity and integrity of the repair effect and reducing project costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330673A_ABST
    Figure CN119330673A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of grouting repair cement mortar, and particularly discloses mortar for grouting repair of pavement slab bottom void and a preparation method of the mortar. The mortar is prepared from the following raw materials: a gel material, water, redispersible latex powder, polypropylene fibers, a water reducing agent, an early strength agent and an expanding agent; the gel material comprises Portland cement, quartz sand, fly ash and heavy calcium carbonate; the water-binder ratio of the water to the gel material is 0.3-0.4. The compressive strength of the mortar prepared by the invention within one day can reach 14.88 MPa, the compressive strength within three days can reach 77.4% of the strength within 28 days, and the breaking strength within three days can reach 94.0% of the strength within 28 days. Due to the characteristic, the repaired road can be quickly put into use, and the traffic interruption time is shortened; the mortar prepared by the invention has high fluidity, the flow value is 15 seconds, irregular gaps and holes can be smoothly filled, and the uniformity and integrity of the repairing effect are ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of grouting repair cement mortar, and in particular to a mortar used for grouting repair of hollows under road panels and a preparation method thereof. Background Art

[0002] Cement concrete pavement is widely used on roads of all grades due to its durability, stability, strong bearing capacity, long service life, low construction and maintenance costs, and suitability for night driving. However, with the rapid increase in traffic volume and heavy axle loads, cement concrete pavements begin to experience various problems such as deterioration, damage, and reduced performance before reaching their designed service life. These problems are caused by factors such as design, construction, and maintenance, and pose a serious risk to the safe use of roads. A common problem with cement concrete pavements is the formation of voids under the road slab. Due to the relatively high stiffness of cement concrete pavements, the cumulative load of vehicle axles can cause some plastic deformation of the underlying structural layer. Water on the road surface enters the underside of the concrete slab through joints or cracks, generating high-pressure water flow that scours the base layer and discharges the base layer particles out of the concrete slab joints, resulting in voids under the concrete slab. When voids form under the slab, the supporting function of the underlying structure is lost, resulting in a cantilever state and increased tensile stress in the slab. Once the stress exceeds a certain level, it will cause the concrete slab to crack or break, resulting in a loss of bearing capacity and reduced pavement performance and fatigue life.

[0003] At present, the main remedial measure for slab voids is slab base grouting, which not only improves the uniformity of the bearing capacity of the pavement base, but also improves the overall bearing capacity of the base. In the grouting reinforcement process, the selection of grouting materials is crucial to achieve effective reinforcement and repair effects. Commonly used grouting materials include inorganic grouting materials, organic modified grouting materials, and organic grouting materials. However, due to high cost, poor fluidity, low strength, and the presence of potential polluting components, organic modified and organic grouting materials are hindered in large-scale applications to solve slab voids.

[0004] Using cement mortar grouting materials to repair voids under cement boards can improve the repair effect while significantly reducing engineering costs, making it one of the most widely used grouting materials. However, when ordinary cement mortar is currently used as a repair material, problems such as insufficient fluidity, insufficient grouting performance, insufficient early strength, and voiding caused by shrinkage often occur. Alternatively, although the fluidity may meet the requirements, the early strength may not meet the standards.

[0005] Therefore, it is necessary to provide a mortar for grouting repair of hollow spaces under road panels and a preparation method thereof, so as to improve the early strength, fluidity and anti-seepage performance of the mortar. Summary of the invention

[0006] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes a mortar for grouting repair of hollows under road panels and a preparation method thereof, thereby improving the early strength, fluidity and anti-seepage performance of the mortar.

[0007] A first aspect of the present invention provides a mortar for grouting repair of voids under road slabs.

[0008] Specifically, the raw materials of the mortar include gel material, water, redispersible latex powder, polypropylene fiber, water reducing agent, early strength agent, and expansion agent; The gel material includes silicate cement, quartz sand, fly ash and heavy calcium carbonate; The water-to-gel ratio of the water to the gel material is 0.3-0.4.

[0009] Preferably, the water-to-gel ratio of the water to the gel material is 0.35-0.4.

[0010] Further preferably, the water-to-gel ratio of the water to the gel material is 0.35, 0.375, or 0.4.

[0011] Preferably, in parts by weight, the raw materials of the mortar include 130-140 parts of gel material, 40-60 parts of water, 0.5-1 part of redispersible latex powder, 0.1-0.3 part of polypropylene fiber, 0.6-0.8 part of water reducing agent, 0.2-0.8 part of early strength agent, and 1-3 parts of expansion agent.

[0012] Further preferably, the raw materials of the mortar include, by weight, 135-140 parts of gel material, 45-60 parts of water, 0.5-1 parts of redispersible latex powder, 0.1-0.3 parts of polypropylene fiber, 0.6-0.8 parts of water reducing agent, 0.2-0.8 parts of early strength agent, and 1-3 parts of expansion agent.

[0013] More preferably, the raw materials of the mortar include, by weight, 137 parts of gel material, 48 parts of water, 0.5 parts of redispersible latex powder, 0.2 parts of polypropylene fiber, 0.6 parts of water reducing agent, 0.8 parts of early strength agent, and 2 parts of expansion agent.

[0014] Preferably, the density of the silicate cement is 3-4 g / cm 3 , with a specific surface area of ​​300~400 m 2 / kg.

[0015] Further preferably, the density of the silicate cement is 3-3.5 g / cm 3 , with a specific surface area of ​​300~350 m 2 / kg.

[0016] More preferably, the density of the silicate cement is 3.18 g / cm 3 , with a specific surface area of ​​350 m 2 / kg.

[0017] Preferably, the standard consistency of the Portland cement is 28-30%.

[0018] Preferably, the standard consistency of the Portland cement is 28-29%.

[0019] Preferably, the standard consistency of the Portland cement is 28.4%.

[0020] Preferably, the content of SiO2 in the quartz sand is 98-99%.

[0021] Further preferably, the content of SiO2 in the quartz sand is 98~98.5%.

[0022] More preferably, the content of SiO2 in the quartz sand is 98.21%.

[0023] Preferably, the density of the quartz sand is 2-3 g / cm 3 .

[0024] Further preferably, the density of the quartz sand is 2.5-3 g / cm 3 .

[0025] More preferably, the density of the quartz sand is 2.63 g / cm 3 .

[0026] Preferably, the sum of the contents of Al2O3 and SiO2 in the fly ash accounts for 80-82% of the total content.

[0027] Further preferably, the sum of the contents of Al2O3 and SiO2 in the fly ash accounts for 81-82% of the total content.

[0028] More preferably, the sum of the contents of Al2O3 and SiO2 in the fly ash accounts for 81.90% of the total content.

[0029] Preferably, the content of SO3 in the fly ash is 1-2%, and the content of CaO is 4-5%.

[0030] Further preferably, the content of SO3 in the fly ash is 1-1.5%, and the content of CaO is 4.5-5%.

[0031] More preferably, the SO3 content in the fly ash is 1.2%, and the CaO content is 4.5%.

[0032] Preferably, the density of the fly ash is 2-3 g / cm 3 , with a specific surface area of ​​5000~5500 m 2 / kg.

[0033] Preferably, the density of the fly ash is 2-2.5 g / cm 3 , with a specific surface area of ​​5200~5300 m 2 / kg.

[0034] Preferably, the density of the fly ash is 2.1 g / cm 3 , with a specific surface area of ​​5260 m 2 / kg.

[0035] Preferably, the content of CaCO3 in the heavy calcium carbonate is 98-99%.

[0036] Further preferably, the content of CaCO3 in the heavy calcium carbonate is 98.5~99%.

[0037] More preferably, the content of CaCO3 in the heavy calcium carbonate is 98.5%.

[0038] Preferably, the MgO content in the heavy calcium carbonate is 0.1-0.5%, and the Al2O3 content is 0.01-0.05%.

[0039] Further preferably, the MgO content in the heavy calcium carbonate is 0.1-0.2%, and the Al2O3 content is 0.01-0.02%.

[0040] More preferably, the MgO content in the heavy calcium carbonate is 0.11%, and the Al2O3 content is 0.01%.

[0041] Preferably, the length of the polypropylene fiber is 2-4 mm.

[0042] Further preferably, the length of the polypropylene fiber is 2-3 mm.

[0043] More preferably, the length of the polypropylene fiber is 3 mm.

[0044] Preferably, the water reducer comprises a polycarboxylate water reducer.

[0045] Preferably, the pH value of the polycarboxylate water-reducing agent is 7-9.

[0046] More preferably, the pH value of the polycarboxylate water-reducing agent is 7.5-8.5.

[0047] More preferably, the pH value of the polycarboxylate water-reducing agent is 8.

[0048] Preferably, the bulk density of the polycarboxylate water reducer is 500-700 kg / lm 3 .

[0049] Further preferably, the bulk density of the polycarboxylate water reducer is 550-650 kg / lm 3 .

[0050] More preferably, the bulk density of the polycarboxylate water reducer is 600 kg / lm 3 .

[0051] A second aspect of the present invention provides a method for preparing mortar.

[0052] Specifically, the steps include: The raw materials of the mortar are stirred and mixed, and then water is added and stirred according to the water-binder ratio, and the mortar is cured and demoulded to obtain the mortar.

[0053] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) The compressive strength of the mortar prepared by the present invention can reach 14.88 MPa within 1 day, the compressive strength within 3 days can reach 77.4% of the strength within 28 days, and the flexural strength within 3 days can reach 94.0% of the strength within 28 days. This feature allows the repaired road to be put into use quickly, reducing the time of traffic interruption; (2) The mortar prepared by the present invention has high fluidity, with a flow value of 15 seconds, and can smoothly fill irregular gaps and cavities, ensuring the uniformity and integrity of the repair effect; (3) The mortar prepared by the present invention has micro-expansion properties, which effectively prevents shrinkage cracking and improves the integrity and durability of the repaired structure; (4) The mortar prepared by the present invention significantly reduces the cost by optimizing the material ratio, has higher economic efficiency, and is suitable for large-scale engineering applications. In addition, the mortar does not contain volatile organic compounds and is friendly to the environment and human health. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] Figure 1 This is a trend chart showing the effect of water-binder ratio on fluidity, compressive strength and flexural strength; Figure 2 This is a trend chart showing the effect of redispersible latex powder on fluidity, compressive strength and flexural strength; Figure 3 This is a trend chart showing the effect of polypropylene fiber on fluidity, compressive strength and flexural strength; Figure 4 This is a trend chart showing the effect of water reducing agent on fluidity, compressive strength and flexural strength; Figure 5 This is a trend chart showing the effect of early strength agent on fluidity, compressive strength and flexural strength; Figure 6 This is a trend chart showing the effect of expansion agent on fluidity, compressive strength and flexural strength; Figure 7 The XRD diffraction results of the mortar prepared in Example 1 at curing ages of 1 d, 3 d, 7 d and 28 d; Figure 8 The SEM photos of the hydration process of the mortar prepared in Example 1 at the curing ages of 1 d, 3 d, 7 d and 28 d; Fig. 9 The EDS spectrum results of the mortar prepared in Example 1 at the curing ages of 1 d, 3 d, 7 d and 28 d; Fig.10 The infrared spectrum test results of the mortar prepared in Example 1 at curing ages of 1 d, 3 d, 7 d and 28 d. DETAILED DESCRIPTION

[0055] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.

[0056] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.

[0057] The silicate cement used is PII 52.5R silicate cement, the quartz sand used is 70-120 mesh quartz sand, the fly ash used is 400 mesh ground fly ash, the heavy calcium carbonate used is 1000 mesh heavy calcium carbonate, the redispersible latex powder is ethylene-vinyl acetate copolymer (EVA) based latex powder, the early strength agent used is triethanolamine organic composite early strength agent, the expansive agent used is sulphoaluminate expansive agent, and the water reducer used is polycarboxylic acid water reducer.

[0058] Example 1 Mortar used for grouting repair of hollow under road slab: by weight, the raw materials of mortar include 137 parts of gel material (100 parts of silicate cement, 27 parts of quartz sand, 3 parts of fly ash, 7 parts of heavy calcium carbonate), 48 parts of water, 0.5 parts of redispersible latex powder, 0.2 parts of polypropylene fiber, 0.6 parts of water reducer, 0.8 parts of early strength agent, and 2 parts of expansion agent. The water-to-gel ratio is 0.35.

[0059] The preparation method comprises the following steps: The raw materials of the mortar are stirred and mixed, and then water is added and stirred at a water-cement ratio of 0.35, and the mixture is placed in a standard curing box for curing, and demoulding is performed to obtain the mortar.

[0060] Example 2 The difference from Example 1 is that, by weight, the amount of water is 51.4 parts, that is, the water-to-gel ratio of water to the gel material is 0.375.

[0061] The addition of other raw materials and the preparation method of mortar are the same as in Example 1.

[0062] Example 3 The difference from Example 1 is that, by weight, the amount of water is 55 parts, that is, the water-to-gel ratio of water to the gel material is 0.40.

[0063] The addition of other raw materials and the preparation method of mortar are the same as in Example 1.

[0064] Example 4 The difference from Example 1 is that, by weight, 0.7 parts of redispersible latex powder are used.

[0065] The addition of other raw materials and the preparation method of mortar are the same as in Example 1.

[0066] Example 5 The difference from Example 1 is that, by weight, 1.0 part of redispersible latex powder is used.

[0067] The addition of other raw materials and the preparation method of mortar are the same as in Example 1.

[0068] Example 6 The difference from Example 1 is that, by weight, 0.1 parts of polypropylene fiber are used.

[0069] The addition of other raw materials and the preparation method of mortar are the same as in Example 1.

[0070] Example 7 The difference from Example 1 is that, by weight, the amount of polypropylene fiber is 0.3 parts.

[0071] The addition of other raw materials and the preparation method of mortar are the same as in Example 1.

[0072] Example 8 The difference from Example 1 is that, by weight, the water reducing agent is 0.7 parts.

[0073] The addition of other raw materials and the preparation method of mortar are the same as in Example 1.

[0074] Example 9 The difference from Example 1 is that, by weight, the water reducing agent is 0.8 parts.

[0075] The addition of other raw materials and the preparation method of mortar are the same as in Example 1.

[0076] Example 10 The difference from Example 1 is that, by weight, the early strength agent is 0.2 parts.

[0077] The addition of other raw materials and the preparation method of mortar are the same as in Example 1.

[0078] Embodiment 11 The difference from Example 1 is that, by weight, the early strength agent is 0.4 parts.

[0079] The addition of other raw materials and the preparation method of mortar are the same as in Example 1.

[0080] Example 12 The difference from Example 1 is that, by mass, the amount of the expansion agent is 1 part.

[0081] The addition of other raw materials and the preparation method of mortar are the same as in Example 1.

[0082] Example 13 The difference from Example 1 is that, by mass, the amount of the expansion agent is 3 parts.

[0083] The addition of other raw materials and the preparation method of mortar are the same as in Example 1.

[0084] Performance testing: 1. Carry out fluidity, compressive and flexural strength tests in accordance with the requirements of "Test method for fluidity of cement paste (inverted cone method)" (T 0508-2005) and national standard "Test method for strength of cement mortar (ISO method)" (GB / T 17671-2021).

[0085] The influence trend of water-binder ratio on fluidity, compressive strength and flexural strength is as follows Figure 1 As shown, among which, Figure 1 As shown in (a), the fluidity of Examples 1 to 3 at different water-binder ratios is between 15.8 and 16 s, with little difference. Figure 1 As shown in (b) and (c), the compressive strength and flexural strength decrease with the increase of the water-to-binder ratio. Therefore, the optimal water-to-binder ratio of the water-to-binder material of the present invention is 0.35.

[0086] The influence trend of redispersible latex powder on fluidity, compressive strength and flexural strength is as follows Figure 2 As shown. Figure 2 As shown in (a), the fluidity of Examples 1 and 4-5 at different redispersible latex powder dosages is between 15.82 and 16 s, with little difference. Figure 2It can be seen from (b) and (c) that the compressive strength decreases with the increase of the redispersible latex powder dosage. The 1 d and 3 d flexural strength decreases with the increase of the redispersible latex powder dosage, and the optimal dosage is Example 1 (0.5 parts by mass), while the 7 d and 28 d flexural strength increases first and then decreases with the increase of the redispersible latex powder dosage. However, the 7 d and 28 d flexural strength of Example 4 with a redispersible latex powder dosage of 0.7 parts is 2.2% and 6.0% higher than that of Example 1 with a dosage of 0.5 parts, respectively, and the increase is not obvious. Therefore, considering the fluidity, compressive strength and flexural strength, the optimal dosage of the redispersible latex powder of the present invention is 0.5 parts.

[0087] The influence trend of polypropylene fiber on fluidity, compressive strength and flexural strength is as follows Figure 3 As shown. Figure 3 As can be seen from (a) in Example 1, when the amount of polypropylene fiber added is 0.2 parts, the fluidity is the largest (the time is the shortest). Figure 3 From (b) and (c), it can be seen that for the 1 d early compressive strength and early flexural strength, the polypropylene fiber of Examples 1 and Examples 6-7 does not change much at different dosages, but the 3 d early compressive strength and early flexural strength increase first and then decrease with the increase of dosage. Since the mortar grouting material requires greater early strength and fluidity, the optimal dosage of the polypropylene fiber of the present invention is 0.2 parts.

[0088] The influence trend of water reducing agent on fluidity, compressive strength and flexural strength is as follows Figure 4 As shown. Figure 4 From (a) in the figure, it can be seen that the fluidity is the largest (the time is the shortest) when the water reducer dosage is 0.6 and 0.7 parts. Figure 4 As shown in (b) and (c), for compressive strength and flexural strength, the strength of Examples 1 and 8-9 shows a downward trend as the water reducer increases. Therefore, considering the fluidity, compressive strength and flexural strength, the optimal dosage of the water reducer of the present invention is 0.6 parts.

[0089] The influence trend of early strength agent on fluidity, compressive strength and flexural strength is as follows Figure 5 As shown. Figure 5 As can be seen from (a) in the figure, the fluidity of Examples 1 and 10-11 increases with the increase of the early strength agent dosage (the time is the shortest). Figure 5 As shown in (b) and (c), the 1-day and 3-day early compressive strength and early flexural strength increase as the early strength agent dosage increases. Therefore, the optimal dosage of the early strength agent of the present invention is 0.8 parts.

[0090] The influence trend of expansion agent on fluidity, compressive strength and flexural strength is as follows Figure 6As shown. Figure 6 As can be seen from (a) in the figure, the fluidity of Examples 1 and 12-13 shows an overall decreasing trend as the amount of early strength agent increases (time increases). Figure 6 From (b) and (c), it can be seen that the 1-day early compressive strength and early flexural strength increase as the expansion agent dosage increases, but the increase is the largest when the expansion agent dosage is 2.0 parts. Therefore, considering the fluidity, compressive strength and flexural strength, the optimal dosage of the expansion agent of the present invention is 2.0 parts.

[0091] 2. The mortar prepared in Example 1 was tested for XRD diffraction at curing ages of 1 d, 3 d, 7 d and 28 d according to the "X-ray Diffraction Analysis Method for Mineral Phase of Portland Cement Clinker" (GB / T40407-2021). The XRD diffraction results are as follows: Figure 7 As shown in the figure, combined with the XRD product analysis results, the SEM photos and EDS spectrum data of the mortar hydration process at curing ages of 1 d, 3 d, 7 d and 28 d were tested. The results are shown in Figure 8 and 9 Finally, infrared spectroscopy tests were performed on the mortars with curing ages of 1 d, 3 d, 7 d, and 28 d. The results are shown in Fig.10 shown.

[0092] Depend on Figure 7 It can be seen that for the mortar with a curing age of 1 day, its hydration products show diffraction peaks of calcium hydroxide, calcium silicate hydrate and quartz, while the diffraction peaks of calcite and ettringite are weak. With the increase of age, the mortar with a curing age of 3 days shows a strong diffraction peak of calcium hydroxide, and the diffraction peak of calcium silicate hydrate is enhanced, which indicates that during the 3-day curing period, the mortar undergoes an intensified secondary hydration reaction, which also indirectly proves the strength test results that the 3-day compressive strength of the mortar can reach 77.4% of the 28-day strength, and the 3-day flexural strength can reach 94.0% of the 28-day strength. The calcium hydroxide diffraction peak of the cement mortar with a curing age of 7 days weakens, and the calcium silicate hydrate diffraction peak further enhances but the increase is weaker than the 3-day diffraction peak, which indicates that the cement hydration product continues to undergo secondary hydration reaction. The diffraction peak of calcium hydroxide in the mortar at the curing age of 28 days is weak, and some diffraction peaks disappear, while calcite, ettringite and calcium silicate hydrate are enhanced to a certain extent, which indicates that the strength growth at 28 days is slow and the maximum strength of the mortar will be reached.

[0093] Depend on Figure 8It can be seen that a large number of hexagonal plate-like crystals appear in the cement mortar at the age of 1 day, and the hexagonal plate-like crystals gradually decrease with the increase of age. This is because a large amount of calcium hydroxide is generated during the cement hydration reaction. Calcium hydroxide is slightly soluble in water, and its concentration in the solution quickly reaches supersaturation and immediately precipitates in the form of hexagonal plate-like crystals. At the same time, a large amount of hydrated calcium silicate gel is generated during the cement hydration reaction. The cross-climbing hydrated calcium silicate gel connects the originally dispersed cement particles and their hydration products to form a three-dimensional space that is firmly combined and dense, and finally forms the strength of cement paste after the cement paste hardens. From the microscopic morphology of cement mortars at different curing ages, it can be seen that a large amount of hydrated calcium silicate gel is generated in the cement mortar at the curing age of 3 days, accompanied by a certain amount of hexagonal plate-like calcium hydroxide; the surface of cement mortars at the ages of 7 days and 28 days is mainly composed of hydrated calcium silicate gel, accompanied by a small amount of hexagonal plate-like calcium hydroxide, which also indirectly shows that the cement mortar has a large early strength.

[0094] Depend on Fig. 9 It can be seen that the calcium-silicon ratio at 1 day is 6.37, and the calcium-silicon ratios at 3 days, 7 days and 28 days are 4.38, 3.85 and 2.01 respectively. That is, with the increase of age, the calcium-silicon ratio of mortar gradually decreases, which shows that the gel decreases with the increase of age. The calcium-silicon ratio from 1 day to 3 days decreased by 31.2%, while the calcium-silicon ratio from 3 days to 7 days only decreased by 12.1%, which shows that a large amount of gel was produced from 1 day to 3 days, and the gelation rate from 3 days to 7 days was weakened. This is also consistent with the trend of strength test results.

[0095] Depend on Fig.10 It can be seen that the -1 and 3440 cm -1 The absorption peaks near 1643 cm represent the OH bond and intermolecular hydrogen bond OH stretching vibration, which are mainly caused by the OH of calcium hydroxide and water; -1 The absorption peak represents the stretching vibration of the C=C double bond, which is mainly caused by the copolymer of ethylene / vinyl acetate in the redispersible latex powder; 1420 cm -1 and 988 cm -1 The absorption peaks of CO3 2- Symmetrical stretching vibration and asymmetric stretching vibration, which are caused by calcium carbonate generated during cement hydration; 1114 cm -1 and 522 cm -1 The absorption peaks at 874 cm are caused by Si-O bending vibration and symmetric stretching vibration, which are mainly caused by Si-O bonds in silicate hydrates and Si-O bonds in quartz; -1 The absorption peak represents the symmetrical stretching vibration of hydrated calcium sulfate. The calcium sulfate hydrate generated by cement hydration produces SO4 2-Group; 712 cm -1 The absorption peaks at 460 cm -1 The absorption peak of 420cm represents the stretching vibration of calcite, which is mainly calcite generated by cement hydration. It is worth noting that in the early stage of curing age, the absorption peak of 420cm -1 The absorption peak mainly represents the stretching vibration of calcite. From the infrared spectrum, it can be seen that the absorption peak types of cement mortars with different curing ages are not much different, which also indirectly shows that the cement mortar generates stable hydration products.

[0096] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution obtained by any modification, equivalent replacement, improvement, etc. made by a person skilled in the art based on the concept of the present invention through logical analysis, reasoning or limited experiments on the basis of the prior art shall be within the scope of protection determined by the claims.

Claims

1. A mortar for grouting repair of hollows under road panels, characterized in that: The raw materials of the mortar include gel material, water, redispersible latex powder, polypropylene fiber, water reducing agent, early strength agent and expansion agent; The gel material includes silicate cement, quartz sand, fly ash and heavy calcium carbonate; The water-to-gel ratio of the water to the gel material is 0.3-0.

4.

2. The mortar according to claim 1, characterized in that In terms of weight, the raw materials of the mortar include 130-140 parts of gel material, 40-60 parts of water, 0.5-1 parts of redispersible latex powder, 0.1-0.3 parts of polypropylene fiber, 0.6-0.8 parts of water reducing agent, 0.2-0.8 parts of early strength agent, and 1-3 parts of expansion agent.

3. The mortar according to claim 1, characterized in that: The density of the silicate cement is 3-4 g / cm 3 , with a specific surface area of ​​300~400 m 2 / kg.

4. The mortar according to claim 1, characterized in that The content of SiO2 in the quartz sand is 98-99%.

5. The mortar according to claim 1, characterized in that: The sum of the contents of Al2O3 and SiO2 in the fly ash accounts for 80-82% of the total content.

6. The mortar according to claim 1, characterized in that The content of CaCO3 in the heavy calcium carbonate is 98-99%.

7. The mortar according to claim 1, characterized in that: The length of the polypropylene fiber is 2-4 mm.

8. The mortar according to claim 1, characterized in that: The water reducing agent includes a polycarboxylate water reducing agent.

9. The mortar according to claim 8, characterized in that The pH value of the polycarboxylate water reducer is 7-9.

10. The method for preparing the mortar according to any one of claims 1 to 9, characterized in that: The following steps are involved: The raw materials of the mortar are stirred and mixed, and then water is added and stirred according to the water-binder ratio, and the mortar is cured and demoulded to obtain the mortar.

Citation Information

Patent Citations

  • Fiber reinforced high-strength mortar used for concrete structure repair

    CN101580369A